1993
DOI: 10.1007/bf03009763
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of vecuronium in patients with and without renal failure: a meta-analysis

Abstract: Eight trials comparing the effects of vecuronium in patients with either normal renal function or renal failure were subjected to a meta-analysis. Vecuronium doses were similar in the different trials, identical in the two patient groups of any given trial, and ranged from 0.05 to 0.14 mg.kg-1. Neuromuscular blockade was assessed by TOF or single twitch stimulation, and recorded by either mechanomyography or electromyography. Indices of blockade included onset time (from injection to maximal twitch depression)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This prolongation of the duration of action of vecuronium may be due to delayed elimination of vecuronium and its active metabolite (3-desacetylvecuronium) as reported by Lynam et al 5 Prolonged duration of action of vecuronium in CRF patients was also confirmed by a meta-analysis of eight clinical studies by Beauvoir et al 12 Our study showed that the duration of action of vecuronium in the anephric patients with severe hyperparathyroidism was shorter than in the patients with CRF who did not require parathyroidectomy. This result is inconsistent with the hypothesis that delayed renal elimination of vecuronium and its metabolite due to CRF may prolong the duration of action of vecuronium, became the renal elimination of vecuronium in anephric patients with severe hyperparathyroidism should be less than that in the CRF patients who did not need the haemodialysis therapy.…”
Section: Discussionmentioning
confidence: 56%
“…This prolongation of the duration of action of vecuronium may be due to delayed elimination of vecuronium and its active metabolite (3-desacetylvecuronium) as reported by Lynam et al 5 Prolonged duration of action of vecuronium in CRF patients was also confirmed by a meta-analysis of eight clinical studies by Beauvoir et al 12 Our study showed that the duration of action of vecuronium in the anephric patients with severe hyperparathyroidism was shorter than in the patients with CRF who did not require parathyroidectomy. This result is inconsistent with the hypothesis that delayed renal elimination of vecuronium and its metabolite due to CRF may prolong the duration of action of vecuronium, became the renal elimination of vecuronium in anephric patients with severe hyperparathyroidism should be less than that in the CRF patients who did not need the haemodialysis therapy.…”
Section: Discussionmentioning
confidence: 56%
“…These results bear little relevance with the reports of Beauvoir and his associates. 38 In the current study, the prolonged duration of vecuronium was speculated to be due to delayed elimination of the drug. Changes in serum potassium and calcium were excluded because of their normal basal values.…”
Section: Scorementioning
confidence: 67%
“…In our view, vecuronium is a perfectly acceptable choice in a patient with compromised renal function but normal hepatic function, who is undergoing a 1-2 h operation, where at most only a very modest prolongation of its neuromuscular blocking effects would be expected (6). Sedating patients in the recovery room and providing mechanical ventilatory support is not without significant attendant risks (e.g., agitation, main stem tracheal intubation, pneumothorax), as well as additional costs to the patient and the healthcare system.…”
Section: Referencesmentioning
confidence: 96%